INTEGRASI TEKNOLOGI KE DALAM KURIKULUM - Suprayekti Suprayekti (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2011)
Facilitating instruction and performance improvement in instruction technology become the objectives of instruction technology to solve learning problems faced by the students. This problem can solved and the objectives can be achieved if the technological resources integrated into the curriculum are used properly. How it is done is to be discussed in this article in detail. The teacher as a curriculum developer should possesses technological competence and knows to choose and use the technology integrated in instruction.